SURGICAL PROCEDURE AND MANAGEMENT OF LARGE MAXILLARY RADICULAR CYST - A CASE REPORT - Velichkovska, Katerina; Mencheva, Zhaklina; Markovska Arsovska, Mirjana; Stojanova, Irena; Temelkova, Simona (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Radicular cysts may constitute up to 70% of all cystic lesions of the jaw, with the incidence of occurrence being in the maxillary region. In fact, cysts are pathological lesions that are lined by epithelium and contain technical or semi-textured material that can range from a translucent yellow to a firm, curd-like mass. The aim of this paper is to present the enucleation of a large radicular cyst in the maxilla in the presence of scant x-ray documentation. The therapeutic approach consisted of opening a mucoperiosteal flap after Pether to access the cyst that had perforated the vestibular lamina. The cyst was completely extirpated using the Partch II method. However, despite the scarce radiological documentation, the oral surgical procedure for enucleation of the cyst was successfully performed. We report a case of 26-year-old male patient with the presence of a large cystic lesion on the right side of the maxilla in the area between the premolar-molar space. Radical surgical approach is the only treatment in most cases of large radicular cysts. Key words: radicular cyst, cystectomy, Partch II, sinus maxillaries, histopathological findings, X-rays recordings.